Paul's evangelion in Galatians 1-2. - Mapangdol, Gloria Lita D. 1971- (Singapore : Trinity Theological College, 2010)
The aim of the study is to demonstrate how evangelion, a terminology which pervades throughout Gal 1-2, is used by Paul in his response to the crisis in Galatia. Since Galatians is not only epistolary, but also rhetorical in character, we have utilized both rhetorical analyses as valuable tools for our study of the text. Galatians 1 and 2 are indeed replete with the evangelion vocabulary, making it a primary consideration when studying Paul's letter to the Galatians. An exegetical analysis shows how Paul emphasizes his gospel in every rhetorical unit in Gal 1-2. Thus, Paul's biographical account (1-15-17), his travels to Arabia, Syria and Cicilia, and his encounters with the pillar apostles in Jerusalem and Antioch are all geared towards Paul's gospel rhetoric.
Paul's answer to the crisis in Galatia is the gospel of Christ. This is not surprising because the crisis in Galatia concerns the gospel itself. The agitators were perverting the gospel by compelling the Gentile Christians to circumcise. we have also argued that the evangelion of the imperial cult cannot be ignored in understanding Paul's gospel an the crisis in Galatia. Hence, at the outset, Paul establishes the singularity of the gospel, its divine origin, and the content, which is the Christ-event 1:4, 7). An analysis of the significance of "the truth of the gospel" adds to Paul's polemics against perversion of the one and only gospel. The phrase appears particularly in Paul's encounter with the pillar apostles in Jerusalem (2:5) and in Antioch (2:14) where issues of circumcision and food laws were discussed. In our analysis of the phrase, we argued that primarily, the phrase means "the truth which is the gospel" (appositive genitive). In the context of Gal 1-2, however, we may also translate "the truth of the gospel" as "the truth originating from the gospel" (genitive of origin) or "the truth given by the gospel" (subjective genitive). What is significant however, is that in all these genitive usages, the truth of the gospel is none other than the Christ-event, which is also an act of God by raising Jesus from the dead (1:1-4). Hence, this gospel becomes the ultimate manifestation of God's free grace and one should not be compromised by the Galatian Christians. Deviating from this gospel means denying the sufficiency of God's free grace through Christ (cf. 5:2). Paul argues that one's standing before God is through christ alone and he represents no alternative.
In light of this, we then argued that the truth of the gospel relates to Paul's concept of justification by faith of Christ. Christ's faithfulness is shown in his willing obedience to God the Father (1:4). Justification through Christ's faithfulness, however, should not reduce Paul's converts to idleness. Just as the gospel cannot be ignored or compromised, responding to the truth of the gospel is also emphasized by Paul. Hence, he persuades the Galatians to be loyal to the gospel even in the face of controversies, internal (e.g. opponents, the Jewish Christians and the pillar apostles or external (e.g. imperial cult).
Submitted to the degree of Doctor of Theology to Trinity Theological College, Singapore
Dissertation (D. Th.) - Trinity Theological College
Keywords: Bible. N.T. Galatians -- Criticism, interpretation, etc